Occupational Safety and Health Interventions to Reduce Musculoskeletal Symptoms in the Health Care Sector - Tullar, Jessica M.; Brewer, Shelley; Amick, Benjamin C.; Irvin, Emma; Mahood, Quenby; Pompeii, Lisa A.; Wang, Anna; Van Eerd, Dwayne; Gimeno, David; Evanoff, Bradley (Journal of occupational rehabilitation, 2010)
Introduction Health care work is dangerous and multiple interventions have been tested to reduce the occupational hazards. Methods A systematic review of the literature used a best evidence synthesis approach to address the general question “Do occupational safety and health interventions in health care settings have an effect on musculoskeletal health status?” This was followed by an evaluation of the effectiveness of specific interventions. Results The initial search identified 8,465 articles, for the period 1980–2006, which were reduced to 16 studies based on content and quality. A moderate level of evidence was observed for the general question. Moderate evidence was observed for: (1) exercise interventions and (2) multi-component patient handling interventions. An updated search for the period 2006–2009 added three studies and a moderate level of evidence now indicates: (1) patient handling training alone and (2) cognitive behavior training alone have no effect on musculoskeletal health. Few high quality studies were found that examined the effects of interventions in health care settings on musculoskeletal health. Conclusions The findings here echo previous systematic reviews supporting exercise as providing positive health benefits and training alone as not being effective. Given the moderate level of evidence, exercise interventions and multi-component patient handling interventions (MCPHI) were recommended as practices to consider. A multi-component intervention includes a policy that defines an organizational commitment to reducing injuries associated with patient handling, purchase of appropriate lift or transfer equipment to reduce biomechanical hazards and a broad-based ergonomics training program that includes safe patient handling and/or equipment usage. The review demonstrates MCPHI can be evaluated if the term multi-component is clearly defined and consistently applied.